PENGARUH FINANCIAL TECHNOLOGY LENDING TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI KALIMANTAN TIMUR: PENGARUH FINANCIAL TECHNOLOGY LENDING TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI KALIMANTAN TIMUR - Yayuk Astuti (ECO-BUILD, 2025)
This study aims to examines the effect of financial technology lending on economic growth in the province of East Kalimantan, the type of data collected is quantitative data on economic growth in the Province of East Kalimantan which is available on the website of the Central Bureau of Statistics in the Province of East Kalimantan and financial technology lending data available on the website of the Financial Services Authority. The analytical method used in this study is classical assumption test analysis, simple regression, coefficient of determination, correlation coefficient, and t-test. The results of the study show that financial technology lending has a positive effect on economic growth in the Province of East Kalimantan. The correlation coefficient of 33.4 percent indicates a effect between financial technology lending and economic growth but not significantly.